Antioxidant Capacities and Total Phenolic Contents of Thymus riatarum. (2019) - Aouam, I.; EL Atki, Y.; Taleb, M.; Taroq, A.; EL Kamari, F.; Lyoussi, B.; Abdellaoui, A.
Abstract: The current study aimed to determine the total phenolic, total flavonoid content and antioxidant property of extracts of Moroccan endemic Thymus riatarum . Four solvent with varying polarities (water, methanol, ethanol and ethyl acetate) were used. The antioxidant activity was evaluated using three separate methods, inhibition of free radical 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing/antioxidant power (FRAP) assays and measurement of total antioxidant capacity. Total polyphenol content was measured using Folin-Ciocalteu assay. Total flavonoids contents were measured by the aluminum chloride colorimetric test. The ethanol extract showed an important antioxidant activity by the two assays: DPPH free radical scavenging activity and total antioxidant capacity with value equal to 0.091±0.02 mg/ml and 425.23±2.05 mg AAE/g DW respectively, which was probably due to its high polyphenols content. The water extract had a higher reducing power than the other extracts with an IC50 value of 0.17±0.025 mg/ml. The present study revealed that Thymus riatarum could be used as an excellent natural source of antioxidant components.